Microstructural elucidation of self-emulsifying system: effect of chemical structure - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2012)
Self-emulsifying systems (SES) emulsify spontaneously to produce fine oil-in-water emulsion when introduced into aqueous phase. The self-emulsification process plays an important role during formation of emulsion. The objective of current work was to understand and explore the inner structuration of SES through controlled hydration and further to study the influence of additive on the same which ultimately governs performance of final formulation in terms of droplet size. Droplet size of final formulations containing structural analogues of ibuprofen was determined. Microstructural properties of intermediate hydrated regimes of SES were investigated using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. The current work established inverse relationship between droplet size of the formulations containing structural analogues of ibuprofen and their Log P values. Microstructural analysis of intermediate hydrated regimes of the prepared samples showed formation of local lamellar structure. Structural analogues of ibuprofen significantly altered microstructure of lamellae which was well correlated with the droplet size of final formulations. In vitro drug release study showed increase in dissolution rate of lipophillic drugs when formulated as SES. The current work emphasizes the fact that tailor-made formulations can be prepared by controlling the properties of intermediate regimes.
Keywords: emulsion; flurbiprofen; ibuprofen; ketoprofen; lamellar structure; self-emulsifying system; structural analogues

Mapping ion-induced mesophasic transformation in lyotropic in situ gelling system and its correlation with pharmaceutical performance - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2013)
To investigate influence of ion induced mesophasic transformation on pharmaceutical performance of in situ gelling system consisting of glyceryl monooleate. The prepared system showed mesophasic transformation during its conversion from sol to gel upon controlled hydration. The process of mesophasic transformation was studied by SAXS, DSC, rheology and plane polarized light microscopy. Further the influence of additives i.e. naproxen salts (sodium and potassium) and naproxen (base) on the process of mesophasic transformation was also elucidated. It was observed that addition of salt form of naproxen transformed W/O emulsions into cubic mesophase whereas addition of base form of naproxen formed reverse hexagonal (H-II) phase upon controlled hydration. The cubic mesophase formed by naproxen salts retarded the drug release for initial 3 h whereas H-II phase showed sustained drug release characteristics for naproxen base following Higuchi drug release kinetics. The current work suggests that formulations with tailor made pharmaceutical performance can be developed by selecting proper additives in the system so as to obtain the desired mesophase `on demand' thereby controlling drug release characteristics.
Keywords: cubic phase; hexagonal phase; liquid crystal; mesophasic transformation; sustained drug release

Micro-structural analysis of NiFe2O4 nanoparticles synthesized by thermal plasma route and its suitability for BSA adsorption - Bhosale, Shivaji V.; Kanhe, Nilesh S.; Bhoraskar, S. V.; Bhat, Suresh K.; Bulakhe, Ravindra N.; Shim, Jae-Jin; Mathe, Vikas L. (Journal of Materials Science-Materials in Medicine, 2015)
The paper presents the experimental studies pertaining to the adsorption of bovine serum albumin (BSA) on the nanoparticles of nickel ferrite (NiFe2O4) with a view of correlating the adsorption properties to their microstructure and zeta potentials. Physical properties of two kinds of nickel ferrites, one synthesized by thermal plasma route and the other by chemical co-precipitation method, are compared. Maximum adsorption (231.57 lg/mg) of BSA onto nickel ferrite nanoparticles, at body temperature (37 degrees C) was observed at pH-value of 5.58 for the thermal plasma synthesized particles showing its higher adsorption capacity than those synthesized by wet chemical means (178.71 mu g/mg). Under the same physical conditions the value of zeta potential, obtained for the former, was higher than that of the latter over a wide range of pH values (3.64-9.66). This is attributed to the differences in the specific surface energies of the two kinds of nanoparticles arising from the degree of crystallinity. The paper presents the experimental evidence for the single crystalline nature of the individual nanoparticles, with mean size of 32 nm, for the thermal plasma synthesized particles as evidenced from the high resolution transmission electron microscopy and electron diffraction analysis. The measurements also reveal the poor crystalline morphology in the chemically prepared particles (mean size of 28 nm) although the X-ray diffraction patterns are not much different. The atomic force microscopy images confirm that the surfaces of plasma synthesized nanoparticles possesses higher surface roughness than that of chemically synthesized one. Presence of adsorbed protein was confirmed by vibrational spectroscopy. The Langmuir adsorption model is found to fit into the experimental data better than the Freundlich adsorption model.